Ecological Awareness Reconstruction in Kuntowijoyo’s Novel Mantra Pejinak Ular - Andwi Sulistiyo (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2020)
Environmental issues have become a topic of discussion in the last few decades. Kuntowijoyo, a well-known novelist in Indonesia, also pays serious attention to the environmental issues through his literary works. This study uses a critical discourse analysis method with an ecocritical approach to reveal and explain the forms of ecological awareness reconstruction which are contained in Kuntowijoyo's novel Mantra Pejinak Ular. The results are as follows. Reconstructions are carried out from a perspective, a way of behaving, a mode of transportation, a model of recreation, and an investment model towards the environment. (1) The reconstruction of the perspective is carried out by rebuilding human consciousness to build harmony with nature. (2) The reconstruction of how to behave is carried out by prioritizing actions to preserve nature. (3) The reconstruction of transportation mode is carried out by warding off the bad social stigma of natural transportation modes. (4) The reconstruction of the recreation model is carried out by enjoying the beauty of animals without cutting them off from their original habitat. (5) The reconstruction of the investment model is carried out by applying an investment model with an ecological perspective that prioritizes environmental sustainability as a legacy for future generations.